1982
DOI: 10.1111/1523-1747.ep12510257
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Langerhans Cells in Human Epidermis during PUVA Therapy: A Morphometric Study

Abstract: Skin biopsies were obtained before and after PUVA therapy from the normal skin of 5 psoriatic patients. By electron microscopic morphometric techniques the pretreatment volume density of Langerhans cells within the epidermis was estimated to be approximately 1%. This density was reduced in all 5 patients after therapy. The volume density of Langerhans cell granules per Langerhans cell cytoplasm was on an average 0.8% and this density was reduced in 4 of the patients after therapy, while in one patient there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In several studies the number of LC in lesional or noninvolved skin of psoriatic patients was reduced or almost depleted after systemic PUVA treatment in several studies [15,[30][31][32][33][34][35][36]. Similar effects were noted after PUVA-bath therapy (both using trimethylpsoralen and methoxypsoralen) [14,35,37] which resulted in a decrease in LCs number in psoriatic epidermis.…”
Section: Discussionmentioning
confidence: 83%
“…In several studies the number of LC in lesional or noninvolved skin of psoriatic patients was reduced or almost depleted after systemic PUVA treatment in several studies [15,[30][31][32][33][34][35][36]. Similar effects were noted after PUVA-bath therapy (both using trimethylpsoralen and methoxypsoralen) [14,35,37] which resulted in a decrease in LCs number in psoriatic epidermis.…”
Section: Discussionmentioning
confidence: 83%
“…It was previously reported that UV induces not only DNA damage in T-cells but also emigration of T-cells from the skin. [101112] However, clinical trials of PUVA and NBUVB treatments for AA have been conducted with variable results. [5678] These therapies are thought to be disadvantageous because large unaffected areas are irradiated along with the AA lesions, resulting in insufficient increment of irradiation dose at lesional skin sites.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that PUVA photochemotherapy (20) and topical use of glucocorticoid drugs (21,22) markedly deplete epidermal Langerhans cells and enhance the rate of repigmentation in patients with nonsegmental type vitiligo. It is well known that PUVA photochemotherapy (20) and topical use of glucocorticoid drugs (21,22) markedly deplete epidermal Langerhans cells and enhance the rate of repigmentation in patients with nonsegmental type vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…In the repigmenting group of patients with vitiligo, the Langerhans cells were markedly depleted in the repigmented skin. It is well known that PUVA photochemotherapy (20) and topical use of glucocorticoid drugs (21,22) markedly deplete epidermal Langerhans cells and enhance the rate of repigmentation in patients with nonsegmental type vitiligo. Thus it is proposed that various methods of treatment which deplete epidermal Langerhans cells may help repigmentation in nonsegmental type vitiligo.…”
Section: Discussionmentioning
confidence: 99%